Ferrite
By adjusting the composition and process of MnZn-based ferrites, ferrites with high saturation magnetic current density and low core loss in the high temperature range are prepared, which solves the problem of large core loss in the prior art and is suitable for automotive applications.
Patent Information
- Application Number
- JP2023173119
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-04
- Publication Date
- 2025-04-16
AI Technical Summary
The existing MnZn-based ferrites have a large core loss in the high temperature range (about 100°C), making it difficult to meet the needs of high DC superposition characteristics and thermal runaway prevention in automotive applications.
55.7 to 58.5 mol% Fe2O3, 34.0-36.0 mol% MnO and the remaining ZnO were used as main components, and 1.55-1.90 wt% NiO, 0.015 wt% or less CaO and 0.010-0.065 wt% Nb2O5 were added as additives to prepare ferrite with an average grain size of 10 to 35 μm and a density of 4.93-4.98 g/cc.
A ferrite with high saturation magnetic current density (450mT or higher) and low core loss (500kW/m3 or lower) in the high temperature range (approximately 100°C) is achieved for magnetic cores in automobiles.
Smart Images

Figure 2025063714000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a MnZn-based ferrite. [Background technology]
[0002] Patent Document 1 discloses an MnZn-based ferrite. The ferrite in Patent Document 1 has a high saturation magnetic flux density at high temperatures of about 100°C. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 4281990 Summary of the Invention [Problem to be solved by the invention]
[0004] When using ferrite for an in-vehicle magnetic core, it is required that the ferrite has high DC superposition characteristics and is easy to suppress thermal runaway in a high temperature range of about 100°C. That is, the ferrite has high saturation magnetic flux density and low core loss in a high temperature range. However, when a conventional ferrite such as that disclosed in Patent Document 1 is used as an in-vehicle magnetic core, there is a problem that the core loss is large in a high temperature range of about 100°C.
[0005] Therefore, an object of the present invention is to provide a ferrite that has a high saturation magnetic flux density and low core loss in a high temperature range of about 100° C. and is suitable for use as a magnetic core. [Means for solving the problem]
[0006] The present invention provides a first ferrite, The main component is 55.7-58.5 mol% Fe. 2 O 3 34.0 to 36.0 mol% MnO, and the remainder ZnO, Additives are 1.55 to 1.90 wt% NiO and 0.015 wt% or less (excluding 0 wt%) SiO 2 and 0.038wt% or less (excluding 0wt%) of CaO and 0.010~0.065wt% of Nb 2 O 5 Including Ferrite is provided.
[0007] The present invention relates to a second ferrite, It is made of a sintered body having an average crystal grain size of 10 to 35 μm, The density of the sintered body is 4.93 to 4.98 g / cc. Ferrite is provided.
[0008] The present invention provides a third ferrite, which is the first ferrite, The DC resistance measured at 100Hz to 5.5MHz and with a current of 0.1mA is 130Ωcm or more. Ferrite is provided.
[0009] The present invention provides a fourth ferrite, which is the first ferrite, The core loss measured at 100℃ in a magnetic field of 100kHz and 200mT is 500kW / m 3 Is less than or equal to Ferrite is provided.
[0010] The present invention provides a fifth ferrite, which is a first ferrite, The saturation magnetic flux density measured at 100℃ in a magnetic field of 1200A / m is 450mT or more. Ferrite is provided. Effect of the Invention
[0011] The saturation magnetic flux density of the ferrite of the present invention is, for example, 450 mT or more when measured in a magnetic field of 1200 A / m at a temperature of 100° C. In addition, the core loss of the ferrite of the present invention is, for example, 500 kW / m when measured in a magnetic field of 100 kHz and 200 mT at a temperature of 100° C.3 Due to the above-mentioned magnetic properties, the ferrite of the present invention is suitable for use as a magnetic core for vehicles. According to the present invention, it is possible to provide a ferrite suitable for a magnetic core having a high saturation magnetic flux density and low core loss in a high temperature range of about 100°C. [Brief description of the drawings]
[0012] [Figure 1] 1 is a perspective view showing a molded ferrite body according to an embodiment of the present invention; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] In general, ferrite is easy to form into any shape and is used for various purposes. In particular, ferrite cores, which are magnetic cores formed from ferrite, have excellent high-frequency characteristics and are widely used. However, when used as magnetic cores for vehicles, ferrite cores must continue to operate normally in high-temperature environments of about 100°C. More specifically, ferrite cores for vehicles are required to have high DC superposition characteristics and to easily suppress thermal runaway in high-temperature ranges of about 100°C.
[0014] In more detail, as vehicles become more electrified, there is a demand for in-vehicle components such as ferrite cores that can operate at higher voltages and currents. Accordingly, the requirements for the heat resistance of ferrite cores are becoming stricter, and ferrite cores that can continue to operate normally in high-temperature environments of around 100°C are being demanded.
[0015] It is unavoidable that the inductance of a ferrite core decreases with increasing temperature. On the other hand, according to the research of the present inventor, by reducing the rate of decrease in inductance in a high temperature range of about 100°C to less than 20%, it is possible to provide a ferrite core that continues to operate normally in a high temperature environment of about 100°C. Furthermore, according to the research of the present inventor, in order to reduce the rate of decrease in inductance in this manner, the ferrite core needs to have a high saturation magnetic flux density of 450 mT or more in a high temperature range of about 100°C. In addition, in order to further improve the reliability of a vehicle, it is necessary to prevent thermal runaway of the ferrite core in a high temperature range of about 100°C. To achieve this, it is necessary to reduce the core loss of the ferrite core in a high temperature range of about 100°C to 500 kW / m 3 It needs to be as follows:
[0016] According to the research of the present inventors, the saturation magnetic flux density is 450 mT or more and 500 kW / m 3 A ferrite core having both of the following core loss characteristics is not known. On the other hand, as described below, the ferrite of the embodiment of the present invention has a high saturation magnetic flux density of 450 mT or more and a low core loss of 500 kW / m 3 Due to these characteristics, the ferrite core of the present embodiment is excellent as an in-vehicle magnetic core.
[0017] With reference to Fig. 1, the ferrite core 14 of the present embodiment is a molded ferrite 10. More specifically, the ferrite 10 is molded into a toroidal shape, and has a cylindrical shape extending along the vertical direction. The vertical direction in the present embodiment is merely a relative direction in which the ferrite core 14 in Fig. 1 extends, and does not need to coincide with the direction of gravity. In addition, the shape of the molded ferrite 10 is not particularly limited.
[0018] The ferrite 10 is made up of a number of sintered bodies 12 produced by sintering ceramic powder. That is, the sintered bodies 12 are produced from ceramic powder, which is a raw material powder. The raw material powder is mainly composed of Fe 2 O3 The raw powders include iron trioxide (Iron Oxide), manganese oxide (MnO), and zinc oxide (ZnO). The raw powders also include nickel oxide (NiO), SiO 2 (Silicon dioxide) powder, CaO (Calcium oxide) powder, and Nb 2 O 5 (Niobium pentoxide) powder is added.
[0019] The ferrite 10 is made of the above-mentioned sintered body 12 and contains, as a main component, Fe 2 O 3 The Fe in Ferrite 10 is ZnO. 2 O 3 When the total content of MnO and ZnO is defined as 100 mol%, Fe 2 O 3 The content of MnO, X1, is 55.7 mol% or more and 58.5 mol% or less, the content of MnO, X2, is 34.0 mol% or more and 36.0 mol% or less, and the content of ZnO, X3, is (100-X1-X2) mol%. That is, ferrite 10 contains 55.7 to 58.5 mol% (including 55.7 mol% and 58.5 mol%) of Fe as a main component. 2 O 3 and 34.0 to 36.0 mol % (inclusive) of MnO, with the remainder being ZnO.
[0020] In addition to the main components mentioned above, Ferrite 10 contains NiO and SiO as additives. 2 , CaO, and Nb 2 O 5 When the total content of the main components in the ferrite 10 is defined as 100 wt%, the content of NiO relative to the main components is 1.55 wt% or more and 1.90 wt% or less, and the content of SiO relative to the main components is 1.55 wt% or more and 1.90 wt% or less. 2 The content of CaO in the main component is greater than 0 wt% and less than 0.038 wt%, and the content of Nb in the main component is greater than 0 wt% and less than 0.015 wt%. 2 O 5The content of is 0.010wt% or more and 0.065wt% or less. That is, ferrite 10 contains, as additives, 1.55 to 1.90wt% (including 1.55wt% and 1.90wt%) of NiO and 0.015wt% or less (excluding 0wt%) of SiO. 2 and 0.038wt% or less (excluding 0wt%) of CaO and 0.010-0.065wt% (including 0.010wt% and 0.065wt%) of Nb 2 O 5 It includes:
[0021] The ferrite 10 of the present embodiment contains only the above-mentioned main components and additives, except for a small amount of inevitable impurities mixed in during the manufacturing process. In other words, the ferrite 10 contains inevitable impurities in addition to the above-mentioned main components and additives. However, the present invention is not limited to this. For example, the ferrite 10 may further contain another additive that is not an inevitable impurity in addition to the above-mentioned additives.
[0022] The above-mentioned main components and additives will be described below.
[0023] Fe 2 O 3 is an essential component for increasing the saturation magnetic flux density of the ferrite 10. 2 O 3 As the content of Fe increases, the saturation magnetic flux density of the ferrite 10 gradually increases, but the core loss of the ferrite 10 also gradually increases. 2 O 3 As the content of Fe increases, the saturation magnetic flux density of the ferrite 10 increases, but the core loss of the ferrite 10 decreases. 2 O 3 The content of is such that the saturation magnetic flux density (450mT) required for an in-vehicle magnetic core can be obtained, and the core loss does not deteriorate significantly (500kW / m 3 From the above viewpoint, it is necessary to keep the Fe 2 O 3The content is preferably 55.7 mol % or more and 58.5 mol % or less, and more preferably 56.7 mol % or more and 57.7 mol % or less.
[0024] Fe 2 O 3 When the content of MnO is within the above-mentioned preferred range, the saturation magnetic flux density of the ferrite 10 can be maximized by keeping the content of MnO within a predetermined range. On the other hand, when the content of MnO is below or above the predetermined range, the saturation magnetic flux density of the ferrite 10 gradually decreases. Therefore, it is preferable that the content of MnO is within the above-mentioned predetermined range. More specifically, the content of MnO is preferably 34.0 mol% or more and 36.0 mol% or less, and more preferably 34.4 mol% or more and 35.4 mol% or less.
[0025] Fe 2 O 3 By adding NiO in a predetermined range together with NiO, it is possible to improve the saturation magnetic flux density while reducing the deterioration of the core loss. On the other hand, when the content of NiO is below or above the predetermined range, the core loss of the ferrite 10 gradually increases, and the saturation magnetic flux density of the ferrite 10 also gradually decreases. Therefore, it is preferable that the content of NiO is within the above-mentioned predetermined range. More specifically, the content of NiO is preferably 1.55 wt% or more and 1.90 wt% or less, and more preferably 1.60 wt% or more and 1.70 wt% or less.
[0026] SiO in a given range 2 By adding SiO, the resistivity (DC resistance value: Ωcm) of the ferrite 10 can be increased, and thus the loss of the ferrite 10 can be reduced. 2 If the content of SiO is below or above the predetermined range, the direct current resistance value becomes small and the core loss of the ferrite 10 deteriorates. 2 It is preferable that the content of SiO is within the above-mentioned range. More specifically, 2The content is preferably 0.015 wt% or less (however, excluding 0 wt%), and more preferably 0.010 wt% or more and 0.015 wt% or less.
[0027] SiO 2 Similarly, the DC resistance value of the ferrite 10 can be increased by adding a predetermined range of CaO. On the other hand, if the CaO content is below or above the predetermined range, the DC resistance value decreases and the core loss of the ferrite 10 deteriorates. Therefore, it is preferable that the CaO content is within the above-mentioned predetermined range. More specifically, the CaO content is preferably 0.038 wt% or less (excluding 0 wt%), and more preferably 0.020 wt% or more and 0.025 wt% or less.
[0028] SiO 2 As with CaO, Nb in a given range is 2 O 5 By adding Nb, the DC resistance of the ferrite 10 can be increased. 2 O 5 If the content of Nb is below or above the specified range, the DC resistance value becomes small and the core loss of the ferrite 10 deteriorates. 2 O 5 The content of Nb is preferably within the above-mentioned range. 2 O 5 The content of is preferably 0.010 wt% or more and 0.065 wt% or less, and more preferably 0.030 wt% or more and 0.050 wt% or less.
[0029] The ferrite 10 of this embodiment can be manufactured as described below.
[0030] First, Fe was used as the raw material powder. 2 O 3 powder, MnO powder, ZnO powder, NiO powder, SiO 2 Powder, CaO powder, and Nb 2 O 5Powder is prepared. Next, the raw material powders are mixed so that the content falls within the above-mentioned preferred range to prepare a mixed powder. Next, the mixed powder is calcined, for example, at a temperature of 1000°C for several hours. Next, the calcined mixed powder is decomposed. Next, the decomposed powder is placed in a mold (not shown) of a predetermined shape and pressed to prepare a molded body of a desired shape. As shown in FIG. 1, the molded body of this embodiment is a toroidal ferrite core 14. Next, in the sintering process, the molded body (ferrite core 14) is sintered.
[0031] As can be understood from the above description, the ferrite core 14 of this embodiment (i.e., the molded body of ferrite 10) can be manufactured by the same manufacturing process as that of a general molded body of ferrite, except for the sintering process. Meanwhile, in the sintering process, the molded body is heated to a holding temperature of about 1290°C, and then held at the holding temperature for a predetermined time. In particular, the oxygen partial pressure is maintained at about 800 ppm until the mixed powder is heated from 600°C to the holding temperature. By maintaining the oxygen partial pressure at about 800 ppm, a dense sintered body 12 can be obtained. In addition, the sintered body density and average crystal grain size of the sintered body 12 can be adjusted by adjusting the oxygen partial pressure.
[0032] Even if the contents of the main components and additives are the same, it is difficult to obtain a desired saturation magnetic flux density if the sintered body density is low. On the other hand, the saturation magnetic flux density can be improved by increasing the sintered body density. More specifically, the sintered body density is preferably 4.93 g / cc or more. However, there is a practical upper limit to the saturation magnetic flux density. The realistic range of the sintered body density is 4.98 g / cc or less.
[0033] In addition to the main components, additives, and sintered body density, the average crystal grain size of the sintered body 12 (the average grain size when the sintered body 12 is approximated as a perfect sphere) also affects the core loss of the ferrite 10. More specifically, even if the contents of the main components and additives are the same, if the average crystal grain size is smaller than 10 μm, the hysteresis loss increases. On the other hand, if the average crystal grain size is larger than 35 μm, eddy currents are more likely to be generated, and eddy current loss increases. Therefore, it is preferable that the average crystal grain size is 10 μm or more and 35 μm or less.
[0034] The ferrite core 14 (i.e., ferrite 10) of the present embodiment is manufactured as described above, and is thus made of a sintered body 12 having an average crystal grain size of 10 to 35 μm (including 10 μm and 35 μm). The sintered body 12 of the present embodiment has a density of 4.93 g / cc or more and 4.98 g / cc or less. In other words, the sintered body density of the ferrite 10 is 4.93 to 4.98 g / cc (including 4.93 g / cc and 4.98 g / cc).
[0035] The contents of main components and additives in conventional ferrites and the sintering process used to manufacture such ferrites result in a low Curie temperature, making it difficult to obtain ferrites with high saturation magnetic flux density and low core loss at high temperatures of around 100°C.
[0036] On the other hand, according to the present embodiment, the Curie temperature of the entire ferrite 10 can be increased by decreasing the proportion of Mn single element ferrite having a low Curie temperature and increasing the proportion of Fe single element ferrite and Ni single element ferrite having a high Curie temperature. 2 O 3 By increasing the content of and adding NiO, the saturation magnetic flux density and the core loss can be improved at the same time. Moreover, according to this embodiment, the average crystal grain size of the sintered body 12 can be made relatively large, thereby reducing the hysteresis loss. Furthermore, by maintaining the oxygen partial pressure at 800 ppm in the sintering process of the ferrite 10, the density of the sintered body of the ferrite 10 can be increased, and thus the saturation magnetic flux density can be further improved.
[0037] More specifically, the DC resistance value measured by applying a current of 100 Hz to 5.5 MHz and 0.1 mA to the fabricated ferrite core 14 (i.e., ferrite 10) is 130 Ωcm or more. Also, the core loss measured at a temperature of 100° C. in a magnetic field of 100 kHz and 200 mT is 500 kW / m 3In addition, the saturation magnetic flux density measured at a temperature of 100° C. in a magnetic field of 1200 A / m is 450 mT or more.
[0038] Due to the above-mentioned magnetic properties, the ferrite 10 of the present embodiment is suitable for use as an in-vehicle magnetic core. According to the present embodiment, it is possible to provide the ferrite 10 suitable as a magnetic core having a high saturation magnetic flux density and a low core loss in a high temperature range of about 100° C. EXAMPLES
[0039] The present invention will now be described in more detail with reference to examples and comparative examples.
[0040] First, ferrite samples of the examples and comparative examples were prepared. 2 O 3 powder, MnO powder, ZnO powder, NiO powder, SiO 2 Powder, CaO powder, and Nb 2 O 5 Next, the raw material powders were mixed so as to obtain the ranges of contents shown in Tables 1 to 14 attached below to prepare mixed powders. Next, the mixed powders were calcined and decomposed, and then a toroidal shaped molded body shown in FIG. 1 was prepared.
[0041] The molded product had a height of 10 mm in the vertical direction and a circular ring shape with a diameter of 25 mm in the horizontal plane perpendicular to the vertical direction. A circular central hole with a diameter of 15 mm was formed in the center of the horizontal plane of the molded product. The central hole penetrated the molded product in the vertical direction.
[0042] Next, the molded body was heated to 1290°C (holding temperature) and then held at the holding temperature for a predetermined time. In particular, the oxygen partial pressure was maintained at about 800 ppm until the mixed powder was heated from 600°C to the holding temperature. At this time, the average crystal grain size and sintered density of the molded body were adjusted by adjusting the oxygen partial pressure.
[0043] The molded bodies of the examples and comparative examples had the above-mentioned shapes. The magnetic properties of the ferrite in the following description were measured using the molded bodies of the above-mentioned shapes. However, the shape of the molded body in the present invention is not particularly limited. Even if the shape of the molded body is different from the above-mentioned shape, it is possible to obtain magnetic properties similar to those in the following description.
[0044] A current of 100 Hz to 5.5 MHz and 0.1 mA was applied to the molded body produced as described above to measure the DC resistance value. The core loss of the molded body was also measured at a temperature of 100°C in a magnetic field of 100 kHz and 200 mT. Specifically, a 5-turn primary coil and a 5-turn secondary coil were wound around the molded body, and the core loss was measured using a BH analyzer. The saturation magnetic flux density of the molded body was also measured at a temperature of 100°C in a magnetic field of 1200 A / m. Specifically, a 40-turn primary coil and a 20-turn secondary coil were wound around the molded body, and the saturation magnetic flux density was measured.
[0045] Tables 1 to 14 show the components, sintered body density, average crystal grain size, saturation magnetic flux density (Bs), core loss (Pcv) and DC resistance of the examples and comparative examples.
[0046] [Table 1]
[0047] [Table 2]
[0048] Referring to Tables 1 and 2, the ferrite of Examples 1 to 5 contains 55.7 mol % or more and 58.5 mol % or less of Fe. 2 O 3 and has a saturation magnetic flux density of 450 mT or more. In particular, the ferrites of Examples 1 to 3 contain 56.7 mol % or more and 57.7 mol % or less of Fe. 2 O 3 The Fe in Comparative Example 1 has a saturation magnetic flux density of about 460 mT. 2O 3 The content of Fe in Comparative Example 2 is less than 55.7 mol%, and the saturation magnetic flux density of the ferrite is less than 450 mT. 2 O 3 The content of exceeds 58.5 mol%, and the saturation magnetic flux density of the ferrite is 450 mT or more, but the DC resistance value is reduced to 100 Ω cm, and the core loss is 490 kW / m 3 It has deteriorated to the point of
[0049] As can be understood from the above explanation, Fe 2 O 3 The content is preferably 55.7 mol % or more and 58.5 mol % or less, and more preferably 56.7 mol % or more and 57.7 mol % or less.
[0050] [Table 3]
[0051] [Table 4]
[0052] Referring to Tables 3 and 4, the ferrites of Examples 1, 6, and 7 contain 34.0 mol% or more and 36.0 mol% or less of MnO, and have a saturation magnetic flux density of about 460 mT. In particular, the ferrites of Examples 1, 6, and 7 contain 34.4 mol% or more and 35.4 mol% or less of MnO. On the other hand, the MnO content of Comparative Examples 3 and 4 is less than 34.0 mol%, and the saturation magnetic flux density of the ferrite is less than 450 mT. Moreover, the MnO content of Comparative Examples 5 and 6 exceeds 36.0 mol%, and the saturation magnetic flux density of the ferrite is less than 450 mT.
[0053] As can be understood from the above explanation, the MnO content is preferably 34.0 mol % or more and 36.0 mol % or less, and more preferably 34.4 mol % or more and 35.4 mol % or less.
[0054] [Table 5]
[0055] [Table 6]
[0056] Referring to Tables 5 and 6, the ferrites of Examples 1, 8 to 10 contain NiO of 1.55wt% or more and 1.90wt% or less, and have a saturation magnetic flux density of 450mT or more. In particular, the ferrite of Example 1 contains NiO of 1.60wt% or more and 1.70wt% or less, and has a saturation magnetic flux density of 460mT. On the other hand, the NiO content of Comparative Examples 7 and 8 is less than 1.55wt%, the saturation magnetic flux density of the ferrite is less than 450mT, and the core loss is deteriorated. Moreover, the NiO content of Comparative Example 9 exceeds 1.90wt%, the saturation magnetic flux density of the ferrite is less than 450mT, and the core loss is deteriorated.
[0057] As can be understood from the above explanation, the NiO content is preferably 1.55 wt% or more and 1.90 wt% or less, and more preferably 1.60 wt% or more and 1.70 wt% or less.
[0058] [Table 7]
[0059] [Table 8]
[0060] Referring to Tables 7 and 8, the ferrites of Examples 1, 11, and 12 contain 0.015 wt% or less of SiO 2 The ferrite of Examples 1 and 12 contains 0.010 wt % or more and 0.015 wt % or less of SiO.2 The ferrite of Comparative Example 10 contains SiO 2 Although the SiO 2 -containing magnets of Comparative Examples 11 to 13 have a saturation magnetic flux density of 450 mT or more, the DC resistance is decreased and the core loss is deteriorated. 2 The content of exceeds 0.015 wt%, and although the saturation magnetic flux density is 450 mT or more, the DC resistance value is decreased and the core loss is deteriorated.
[0061] As can be understood from the above explanation, SiO 2 The content of is preferably 0.015 wt% (however, excluding 0 wt%), and more preferably 0.010 wt% or more and 0.015 wt% or less.
[0062] [Table 9]
[0063] [Table 10]
[0064] Referring to Tables 9 and 10, the ferrites of Examples 1, 13 to 15 contain 0.038wt% or less of CaO, and have a DC resistance value of 130Ωcm or more while maintaining a saturation magnetic flux density of 450mT or more. In particular, the ferrites of Examples 1 and 14 contain 0.020wt% or more and 0.025wt% or less of CaO, and have a DC resistance value of 140Ωcm or more while maintaining a saturation magnetic flux density of 460mT or more. On the other hand, the ferrite of Comparative Example 14 does not contain CaO and has a saturation magnetic flux density of 450mT or more, but the DC resistance value is reduced and the core loss is deteriorated. Moreover, the CaO content of Comparative Examples 15 and 16 exceeds 0.038wt%, the saturation magnetic flux density is less than 450mT, and the DC resistance value is reduced and the core loss is deteriorated.
[0065] As can be understood from the above explanation, the CaO content is preferably 0.038 wt% (however, excluding 0 wt%), and more preferably 0.020 wt% or more and 0.025 wt% or less.
[0066] [Table 11]
[0067] [Table 12]
[0068] Referring to Tables 11 and 12, the ferrite of Examples 1 and 16 to 19 contains 0.010 wt% or more and 0.065 wt% or less of Nb. 2 O 5 The ferrite of Examples 1 and 16 contains 0.030 wt % or more and 0.050 wt % or less of Nb, and has a DC resistance of 130 Ωcm or more while maintaining a saturation magnetic flux density of 450 mT or more. 2 O 5 It has a saturation magnetic flux density of 460 mT and a DC resistance value of 140 Ωcm or more. 2 O 5 The content of Nb in Comparative Examples 17 and 18 is less than 0.010 wt%, and although the saturation magnetic flux density is 450 mT or more, the DC resistance value is decreased and the core loss is deteriorated. 2 O 5 The content exceeds 0.065 wt, the saturation magnetic flux density is less than 450 mT, the DC resistance value is reduced, and the core loss is deteriorated.
[0069] As can be understood from the above explanation, Nb 2 O 5 The content of is preferably 0.010 wt% or more and 0.065 wt% or less, and more preferably 0.030 wt% or more and 0.050 wt% or less.
[0070] [Table 13]
[0071] [Table 14]
[0072] Referring to Tables 13 and 14, the sintered density of the ferrite of Examples 1 and 20 to 24 is 4.93 g / cc or more and 4.98 g / cc or less, and the ferrite has a saturation magnetic flux density of 450 mT or more. On the other hand, the sintered density of the ferrite of Comparative Examples 20 to 22 is less than 4.93 g / cc, and the saturation magnetic flux density is less than 450 mT.
[0073] The average crystal grain size of the ferrite in Examples 1 and 20 to 24 is 10 μm or more and 35 μm or less, and the ferrite has a saturation magnetic flux density of 450 mT or more. On the other hand, the average crystal grain size of the ferrite in Comparative Example 21 exceeds 35 μm, the saturation magnetic flux density is less than 450 mT, and the core loss is 500 kW / m 3 Moreover, the average crystal grain size of the ferrite of Comparative Example 22 is less than 10 μm, and the saturation magnetic flux density is less than 450 mT.
[0074] As will be understood from the above explanation, the ferrite preferably has a sintered density of 4.93 g / cc or more and 4.98 g / cc or less, and an average crystal grain size of 10 μm or more and 35 μm or less. [Explanation of symbols]
[0075] 10 Ferrite 12 Sintered body 14 Ferrite core
Claims
1. The main component is 55.7 to 58.5 mol% Fe. 2 O 3 34.0 to 36.0 mol % MnO, and the balance ZnO; Additives: 1.55 to 1.90 wt% NiO and 0.015 wt% or less (excluding 0 wt%) SiO 2 0.038wt% or less (excluding 0wt%) of CaO, and 0.010-0.065wt% of Nb 2 O 5 Including Ferrite.
2. The ferrite according to claim 1, The sintered body has an average crystal grain size of 10 to 35 μm. The density of the sintered body is 4.93 to 4.98 g / cc. Ferrite.
3. The ferrite according to claim 1, The DC resistance measured with a current of 100 Hz to 5.5 MHz and 0.1 mA is 130 Ωcm or more. Ferrite.
4. The ferrite according to claim 1, The core loss measured at 100°C in a magnetic field of 100 kHz and 200 mT is 500 kW / m 3 Is less than or equal to Ferrite.
5. The ferrite according to claim 1, The saturation magnetic flux density measured at 100°C in a magnetic field of 1200 A / m is 450 mT or more. Ferrite.
Citation Information
Patent Citations
ferrite material
JP4281990B2